Application of Plant-Based Metal Nanomedicine in Treatment of Various Types of Cancer: A Review - Jihan Nurafifah Hernawan; Ratnaningsih Eko Sardjono (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Plant-based nanomedicine is a rapidly growing field of research that utilizes plant-derived nanoparticles for the treatment of cancer. Nanoparticles from plant extracts have a number of advantages over synthetic nanoparticles, including biocompatibility, low toxicity, and ease of synthesis Objective: This article comprehensively explores the synthesis, characterization, and anticancer activities of silver nanoparticles (AgNPs), zinc oxide nanoparticles (ZnO-NPs), and gold nanoparticles (AuNPs) synthesized using various plant extracts Methods: The research method used in this article is Systematic Literature Review (SLR). The research method used in this article is the Systematic Literature Review (SLR). The data are collected using Harzing’s Publish or Perish. The included literature sources discuss the synthesis and characterization of plant-based nanoparticles as anticancer, are published within the last 5 years, and are indexed in Google Scholar Results: Various synthesis methods influence the properties and cytotoxic effects of silver, zinc oxide, and gold nanoparticles derived from plant extracts. Characterization techniques provide insights into their synthesis, morphology, crystalline structure, surface chemistry, and stability. Conclusion: The results of this study reveal that silver nanoparticles (AgNPs), zinc oxide nanoparticles (ZnO-NPs), and gold nanoparticles (AuNPs) synthesized from plants have great potential in the treatment of various types of cancer.